Effect of urchin-like gold nanoparticles in organic thin-film solar cells. Issue 27 (24th June 2016) - Pangdam, Apichat; Nootchanat, Supeera; Ishikawa, Ryousuke; Shinbo, Kazunari; Kato, Keizo; Kaneko, Futao; Thammacharoen, Chuchaat; Ekgasit, Sanong; Baba, Akira
Abstract : A schematic of the fabricated UL-AuNP-enhanced OSCs. Abstract : In this study, urchin-like gold nanoparticles (UL-AuNPs) are used in the fabrication of organic thin-film solar cells (OSCs). UL-AuNPs, which have gold nanothorns on their surface, enhance light accumulation by acting as light-trapping materials. This is due to the enhanced electric field and light scattering attributed to the nanothorns on the surface of the nanoparticles. UL-AuNPs were incorporated into a poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) thin-film layer of organic thin-film solar cells (OSCs). UV-vis spectra, atomic force microscopy (AFM) images, current density versus voltage properties, and the impedance spectra of the fabricated devices were recorded at various concentrations of UL-AuNPs. We found that the efficiency of the OSCs with UL-AuNPs was not only higher than that of a reference cell without nanoparticles but also higher than that of OSCs with spherical AuNPs. Finite-difference time-domain (FDTD) simulation indicated that the electric field around the UL-AuNPs increased due to the presence of nanothorns.